Method of health education for deaf: A systematic review - Ajeng Galuh Wuryandari; Muhammad Rusdi; Asni Johari; Guspianto Guspianto (Shahrekord University of Medical Sciences, 2024)
Background and aims: Healthcare establishments must treat people who are deaf or hard of hearing equally. As several experimental studies have yielded different outcomes, some studies on health education techniques must be conducted to examine the effects of health education on hearing loss. This study outlines how researchers educate deaf people about health issues. Methods: This study was conducted in June 2023 in Jambi, Indonesia. A comprehensive search strategy for each database was developed using the following search terms: "deaf," "hearing impairment," "health education," "adolescent," and "adult." A comprehensive assessment of the references from all the studies included in the analysis was also conducted. The forthcoming PRISMA 2020 rules are approaching. Researchers employ Roanalyze to analyze the potential for bias in a study and use the Critical Appraisal Skills Programme (CASP) to evaluate the authenticity of the study. The writers autonomously acquired the data, whereas external sources reassessed and evaluated the results. Results: The review database successfully incorporated twenty-one studies relevant to its themes and objectives. Sign language plays a crucial role in health education by enhancing communication and literacy for deaf individuals through visual learning methods and telemedicine. Conclusion: Sign language plays an essential role in health education, as it improves accessibility for deaf individuals by utilizing visual aids and multimedia-based approaches to learning.